Cardiac Transplantation following Cobalt Cardiomyopathy from Bilateral Metal-on-Metal Hip Replacements. (8th June 2022) - Szedlak, Peter; Virdi, Amrik; Cacciottolo, Paul; Shepherd, Stephen; Pettit, Stephen; Falter, Florian
Abstract : A fifty-two-year-old man underwent heart transplantation at our centre after four years of developing progressive heart failure symptoms due to cobalt toxicity-related cardiomyopathy. Between the ages of forty and forty-two, he underwent bilateral metal-on-metal hip arthroplasties for early onset osteoarthritis. Six years later, he developed increasing fatigue and pericardial effusions. Following a prolonged period of deterioration without a clear cause, the diagnosis of cobalt toxicity-related cardiomyopathy due to cobalt-chromium alloy hip prostheses was eventually made. He underwent bilateral revision hip arthroplasties and was listed for heart transplantation. Metal-on-metal joint replacement is a rare cause of iatrogenic cobalt toxicity. Anaesthetists may encounter patients with unexplained symptoms of heart failure, having a high index of suspicion presenting an opportunity for early diagnosis and intervention before end-stage disease develops.